A behavioral approach to modelling strategy execution: The role of organizational support and the moderated mediation effect of engagement and communication - Chuah, Francis; Teoh, Kenny Guan Cheng; Ting, Hiram; Lau, Evan (2016)
Much of the failure in strategy execution in organization is attributed to human factors. While there is abundance of studies which delve into strategy execution, literature pertaining to the behavioral strategy and its impact on strategy execution remains scarce. Interest towards behavioral strategy is recently renewed as a result of the rising concern of the non-progressive rate of successful strategy implementation in the practicing world. This study answers the call for more research on behavioral strategy by examining the role of engagement, a concept drawn from the theory of engagement and work-psychology literature, in explaining the support-execution relationship. Subsequently, the support-execution model of strategy execution is advanced by a joint investigation of the mediating role of strategy engagement as well as the moderating role of strategy communication in the mediated relationship. Using process macro in Statistical Package for Social Sciences, the model was tested with 224 middle level managers selected from the service industry in Malaysia. The result shows that strategy engagement mediates the relationship between organizational support and strategy execution. Moreover, strategy communication is found to moderate the relationship between firstly organizational support and strategy execution, and secondly strategy engagement and strategy execution. The moderated mediation analysis reveals that strategic communication moderates the mediated relationship between organizational support and strategy execution via strategy engagement. Results from the integrated moderated mediation model provide new insights into the interaction of behavioral variables and their effect on strategy execution in contemporary business environment.